Dushinckanus mesopotamicus, a new species of Myodochini from Argentina (Heteroptera: Lygaeoidea: Rhyparochromidae) - Dellapé, Pablo Matías; Melo, María Cecilia (Zootaxa, 2005)
Dushinckanus mesopotamicus, a new myrmecomorphic species from Argentina, is described. The male genitalia are described and illustrated and the phylogenetic relationships of the genus are discussed.